INVESTASI DI PASAR MODAL BERDASARKAN LAPORAN KEUANGAN DAN HARGA SAHAM - Setyaningsih Sri Utami (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2008)
Abstract Capital market is activity bringing into contact between long-range fund buyer and seller in order to developing its effort. In executing its economics function, capital market provide facility to remove fund from lender to borrower, expected of is existence of capital market will be able to become fund gathering alternative besides banking system. Capital market enablecompany publish securities that are in the form of debt sign letter and or proprietary marking letter share. Important information which it is important to know investor candidate before doing investment capital market that is shall have knowledge company financial statement information and share price. To investor represent consideration, do profiting to buy pertinent company share or price of stocks. Analysis represent matter which very base, which must be done by investor before doing conducting investment at share. Without rational and accurate analysis of possibility all capital owner. will obtain get bigger loss. Decision to buy share happened when estimate value intrinsic value above market price, on the contrary decision sell share happened when estimate value under market price, therefore, determining capital owner price of stocks have to analyze beforehand to share exist in stock market utilize to determine which share or portfolio which is how which can give advantage most optimal Keywords: debt to equity ratio, cost of capital, investor, fundamental analysis, technical analysis, net assets approach, investment opportunity approach.